Analisis Pemerolehan Bahasa Pada Anak Usia 6 Tahun 1 Bulan Berdasarkan Mean Length Of Utterance dalam Aspek Fonologi Morfologi dan Sintaksis - Siti Rodiyah; Hendra Setiawan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research is motivated by the importance of understanding children's language development as an indicator of their cognitive and social abilities. The study aims to analyze language acquisition in a 6-year-1-month-old child through Mean Length of Utterance (MLU) measurement, focusing on phonological, morphological, and syntactic aspects. The method used is descriptive qualitative with data collection techniques including observation, recording, and conversation transcripts. The results show that the research subject has MLU values appropriate to their age development stage. They have good phonological ability in pronouncing almost all Indonesian phonemes, morphological mastery including basic affixes usage, and syntactic ability in forming compound sentences. This study concludes that MLU is an effective measurement tool for children's language acquisition and recommends using this method for monitoring language development in preschool-aged children.